Impact of Youtube and Video Podcast on listening comprehension among young learners - Yaacob, Aizan; Amir Amir, Amira Shazmin; Mohd Asraf, Ratnawati; Mohd Yaakob, Mohd Faiz; Mohamad Zain, Farah (International Journal of Interactive Mobiles Technologies, 2021)
Even though listening comprehension is an important language skill in second language learning, it is considered to be the most difficult skill to learn. Besides, the teaching of listening comprehension among primary pupils is often neglected even though the role of listening comprehension in language teaching has been repeatedly emphasized. Using an action research design, this study explores the teaching of listening comprehension utilizing YouTube and Video-Podcast involving 40 Primary Year 4 pupils from one of the cluster schools of excellence in the northern region of Malaysia. This study attempts to investigate to what extent did the use of YouTube and Video-Podcast enhance Primary Year 4 pupils’ listening comprehension. This study adopted multiple data collection methods including pre-post tests, reflection, observation, and focused group interviews. However, the data analysis section was mostly pre and post tests data and observation. Only these data collection and analysis tools will be expanded in this study, and not the reflection and focus group interviews. The quantitative data were analyzed statistically using paired sample t-test while thematic analysis was used for analyzing the qualitative data. The findings revealed that YouTube and Video-Podcast yielded positive significant impact on listening comprehension skills among Primary ESL pupils. There was statistically significant increase in listening comprehension scores from pre-test and post-test. Four themes emerged from the observation data. It increased learners’ participation and understanding, developed team spirit as well as enhanced interest and motivation of the young learners